Cone beam computed tomography in Endodontics – a review of the literature. (9th April 2019) - Patel, S.; Brown, J.; Pimentel, T.; Kelly, R. D.; Abella, F.; Durack, C.
Abstract: The use of cone beam computed tomography (CBCT) in the diagnosis and/or management of endodontic problems is increasing and is reflected in the exponential rise in publications on this topic in the last two decades. The aim of this paper is to: (i) Review current literature on the endodontic applications of CBCT; (ii) Based on current evidence make recommendations for the use of CBCT in Endodontics; (iii) Highlight the areas in which more research is required.